High thermal stability Si-Al based N-carrier for efficient and stable chemical looping ammonia generation. (1st October 2022) - Xiong, Chuhao; Wu, Ye; Feng, Mingqian; Fang, Jing; Liu, Dong; Shen, Laihong; Argyle, Morris D.; A. M. Gasem, Khaled; Fan, Maohong
Graphical abstract: Highlights: The cyclic N-sorption/desorption characteristics of the N-carriers were studied. The Si-modified Al2 O3 N-carrier enhanced the cyclic N-sorption/desorption performance. Loading Si-modified Al2 O3 N-carrier on ZrO2 could increase the NH3 yield and selectivity. The nitriding and ammoniating conversion efficiency maintained at about 71% and 60% respectively in five cycles. Abstract: Chemical looping ammonia generation (CLAG) is a promising NH3 production technology due to its potential for high yield of NH3 and low CO2 emission footprint. However, the stabilities of the existing N-carriers are problematic during the cyclic N-sorption/desorption. This research was designed to overcome that challenge through use of elemental doping and depositing the N-carrier on a support. The experimental results show that the N-sorption/desorption performance of γ-Al2 O3 N-carriers decreased with cycling due to the deterioration of the pore structure and phase transformation. A Si-modified alumina-based N-carrier, with a Si: Al molar ratio of 1:20 prepared by co-precipitation, was much more resistant to high-temperature phase transition and collapse of pore structure, resulting in highly stable cyclic N-sorption/desorption performance. Use of ZrO2 as a support for the Si-modified Al-based N-carrier further reduced NH3 decomposition and thus increased the NH3 yield and selectivity by 85.6% and 53.6% compared to that obtained with the pure γ-Al2 O3 N-carrier.